Glider monitoring of shelf suspended particle dynamics and transport during storm and flooding conditions. (15th October 2015) - Bourrin, François; Many, Gaël; Durrieu de Madron, Xavier; Martín, Jacobo; Puig, Pere; Houpert, Loic; Testor, Pierre; Kunesch, Stéphane; Mahiouz, Karim; Béguery, Laurent
Abstract: Transfers of particulate matter on continental margins primarily occur during energetic events. As part of the CASCADE (CAscading, Storm, Convection, Advection and Downwelling Events) experiment, a glider equipped with optical sensors was deployed in the coastal area of the Gulf of Lions, NW Mediterranean in March 2011 to assess the spatio-temporal variability of hydrology, suspended particles properties and fluxes during energetic conditions. This deployment complemented a larger observational effort, a part of the MOOSE (Mediterranean Ocean Observing System of the Environment) network, composed of a coastal benthic station, a surface buoy and moorings on the continental slope. This set of observations permitted to measure the impact of three consecutive storms and a flood event across the entire continental shelf. Glider data showed that the sediment resuspension and transport observed at the coastal station during the largest storm ( H s >4 m) was effective down to a water depth of 80 m. The mid-shelf mud belt, located between 40 and 90 m depth, appears as the zone where the along-shelf flux of suspended sediment is maximum. Besides, the across-shelf flux of suspended sediment converges towards the outer limit of the mid-shelf mud belt, where deposition of suspended particles probably occurs and contributes to the nourishment of this area. Hydrological structures, suspended particles transport and properties changed drastically during stormy periods and the following flood event. Prior to the storms, the shelf waters were weakly stratified due in particular to the presence of cold dense water on the inner- and mid-shelf. The storms rapidly swept away this dense water, as well as the resuspended sediments, along the shelf and towards a downstream submarine canyon. The buoyant river plumes that spread along the shelf after the flooding period provoked a restratification of the water column on the inner- and mid-shelf. The analysis of glider's optical data at different wavelengths suggests that the coastal area and the bottom nepheloid layer during the largest storm are primarily composed of coarse particles, probably macroflocs, and that the size of particles decreases further offshore. A similar trend, albeit less contrasted, is observed after the flooding. This work provided a unique synoptic view across the entire shelf of the impact of a typical Mediterranean storm on bottom sediment erosion and particulate fluxes. Repeated glider transects across the south-western part of the Gulf of Lions shelf permitted for the first time to measure continuously the thermo-haline structures, the suspended particles concentrations and size, the current speed, and to estimate the particulate transport before, during and after typical Mediterranean storm events. Glider data complement and compare well with concomitant high frequency time series at fixed stations along the coast and in a downstream submarine canyon. Graphical abstract: Highlights: Coastal hydrology was monitored using a glider during storm and flood conditions. Significant shelf sediment resuspension and transport were observed until 80 m depth. Suspended sediment along-shelf fluxes are maximum within the mid-shelf mud belt. Storm induced downwelling of dense shelf water towards adjacent canyon. Glider optical data revealed that bottom nepheloid layer is composed of macroflocs.